2020
DOI: 10.3390/w12072066
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Responses of the Asian Reservoir to Long-Term Seasonal and Interannual Dynamic Monsoon

Abstract: The main objectives of the study were to determine the trophic response of the temperate reservoir to seasonal and interannual variabilities of monsoon inorganic solids and nutrients along the gradients of the morphologically complex Asian reservoir using long-term datasets between 2000–2018. Nutrient regime (total nitrogen—TN, total phosphorus—TP), total suspended solids (TSS), and chlorophyll-a (CHL-a) were primarily affected by an intensity of summer monsoon and the longitudinal structure of riverine (Rz), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Although CHL-a disclosed a similar development as TP, it is essential to mention an overall decline in the annual CHL-a levels during the study period, mostly post 2015 drought year it is showed a sharp decline. A valid reason for this decline could be the successive increase in annual rainfall that could have washed out most of the algal CHL-a [ 12 ]. TSS disclosed varied loads to the yearly fluctuating precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CHL-a disclosed a similar development as TP, it is essential to mention an overall decline in the annual CHL-a levels during the study period, mostly post 2015 drought year it is showed a sharp decline. A valid reason for this decline could be the successive increase in annual rainfall that could have washed out most of the algal CHL-a [ 12 ]. TSS disclosed varied loads to the yearly fluctuating precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…These results approximate the spatial dynamics of nutrients, algal CHL-a and organic pollution indicators in reservoir zones and water intake tower sites. This is important to mention the due to the almost no relation with TN, the chances of collinearity are minor, and the system is strongly P-limited [ 12 , 35 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings showed the nutrient loadings from watersheds caused by extreme rainfall events that increased the algal CHL-a growth [21,[54][55][56]. The increasing TSS levels, BOD, TP, and CHL-a during the flood years declined, indicating intensive rainfall mediated dilution [20,46,57,58].…”
Section: Role Of Monsoon and Water Chemistry Variabilitymentioning
confidence: 98%